The mediatory role of challenge and threat in the relationship between positive thinking skills and perception of excellent performance: a study on football players - Pepe, Osman; Koc, Mustafa Can; Ayhan, Cihan; Talaghir, Laurentiu-Gabriel; Bentea, Cristina-Corina (Frontiers in Psychology, 2025)
PurposeThe present study aims to examine the mediating role of challenge and threat between positive thinking skills and perception of excellent performance in football players competing in the regional amateur league, which is referred to as a semi-professional league in Turkey.MethodsThe study population consisted of football players competing in regional amateur leagues in the 2023–2024 season, and the sample consisted of 388 athletes selected using the simple random method. In addition to the demographic information form developed by the researcher, the Positive Thinking Skills Scale, the Challenge and Threat in Sport Scale and the Performance Perfectionism Scale for Sport were applied to the participants. The data were analyzed digitally through the SPSS 25 package program. The Pearson Correlation analysis was used to determine the correlations between the variables and a regression analysis of the indirect effect approach based on the Bootstrap method through PROCESS v4.2 macro was used to determine the mediating effect of challenge and threat in the relationship between positive thinking and perception of excellent performance. PROCESS Macro Model Option 4 developed by Hayes was used to examine the mediating effect. While conducting this analysis, the 5,000 resampling option was selected in the Bootstrap method.ResultsThe study found that positive thinking had a positive, moderate, and statistically significant effect on the perception of challenge (a = 0.439, p < 0.01) and excellent performance (c’ = 0.484, p < 0.001), with approximately 32% of the variance in challenge explained by positive thinking (R2 = 0.319, p < 0.01). Additionally, challenge played a mediating role. Positive thinking also had a negative, moderate effect on threat (a = −0.425, p < 0.01), explaining 7% of the variance in threat (R2 = 0.070, p < 0.01). However, the threat had a negative and low-level impact on the perception of excellent performance (b = −0.244, p < 0.001).ConclusionIn conclusion, it was found that the positive thinking skills of the football players positively affected their perceptions of excellent performance, and the feelings of challenge and threat they experienced on the field played a mediating role in the relationship between these positive thinking skills and perceptions of excellent performance.